Mind the gap: The timeline as a narrative frame for personal content - Lindley, Siân (2013)
This paper presents initial findings from a deployment of Timecard, a system for the production of personal timelines. The data reveal that, far from being a neutral structure for the organisation of personal content, the timeline carries a particular set of conventions that encourage balance and that communicate precision. Yet these two values are at odds with each other. Creating a coherent timeline can mean omitting accurate content, as well as including that which is ambiguous. Resolving this mismatch is a challenge for design.
CHI 2013 workshop Avec le Temps! Time, Tempo, and Turns in Human-Computer Interaction